Analisis Penggunaan Disfemia di Gampong Paya Kruep Kecamatan Darul Falah Kabupaten Aceh Timur - Marzuki, Maulidar; Ahyar, Juni; Rahayu, Ririn (FKIP Universitas Palangka Raya, 2026)
This study aims to describe the types and functions of dysphemism usage in the Acehnese language within Paya Kruep Village (Gampong), Darul Falah Sub-district, East Aceh Regency. This research utilizes a qualitative research method. The data in this study are the utterances from community interactions in Gampong Paya Kruep, Darul Falah Sub-district, East Aceh Regency. The data collection techniques employed in this research are observation, documentation, listening (simak), and recording techniques. The data analysis technique uses the theory of Miles and Huberman, which includes data reduction, data display, and conclusion drawing. Based on the research results, a total of 39 utterances containing dysphemistic elements were found across all data. Several utterances were in the form of appellations/nicknames related to actual physical characteristics, numbering five data points. Seven other data points were terms containing insult or disrespect. Furthermore, there were ten data points showing the comparison of humans to animals, which demonstrates the community's tendency to use harsh metaphors in interactions. Dysphemism also appeared in the form of taboo terms, totaling four data points, while nine other data points were appellations or direct slurs directed at the interlocutor. Meanwhile, four other data points were in the form of oaths or curses, reflecting the emotional expressions of the speakers. The functions of dysphemism found are also diverse, corresponding to their context of use. Out of the 39 data points, nine function to indicate the speaker's annoyance, five other data points are used to provide emphasis on a specific intent, and ten data points function to affirm or reinforce the meaning intended to be conveyed. The most dominant number, which is fifteen data points, shows that dysphemism is most frequently used to express anger or frustration.Keywords: Semantics, Dysphemism, Acehnese language.